2019
DOI: 10.1111/hiv.12834
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of presentation and survival of HIV‐infected patients admitted to a tertiary‐level intensive care unit

Abstract: ObjectivesCompared to other countires internationally, South Africa has the largest number of people living with HIV. There are limited data in developing countries on the outcomes of HIV-infected patients in the intensive care unit (ICU). The objectives of this study were to describe the pattern of presentation of these patients and to determine factors that may influence survival to ICU discharge. MethodsThe medical charts of 204 consecutive HIV-infected individuals who were admitted to the Charlotte Maxeke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
2
11
0
6
Order By: Relevance
“…29 With regard to other significant study findings, the relatively high number of participants with an elevated CRP (84.5%), hypoalbuminemia (60.8%), hyperlactatemia (42%), thrombocytopaenia (19.9%) and a high qSOFA score (17.5%) is in line with the large number of participants presenting with severe illnesses. Previous studies have shown that elevated CRP, 31 albuminemia, 32 hyperlactatemia, 33 thrombocytopaenia 34 and higher qSOFA scores 35,36 were predictors of mortality and poor outcomes in HIV-positive individuals.…”
Section: Discussionmentioning
confidence: 96%
“…29 With regard to other significant study findings, the relatively high number of participants with an elevated CRP (84.5%), hypoalbuminemia (60.8%), hyperlactatemia (42%), thrombocytopaenia (19.9%) and a high qSOFA score (17.5%) is in line with the large number of participants presenting with severe illnesses. Previous studies have shown that elevated CRP, 31 albuminemia, 32 hyperlactatemia, 33 thrombocytopaenia 34 and higher qSOFA scores 35,36 were predictors of mortality and poor outcomes in HIV-positive individuals.…”
Section: Discussionmentioning
confidence: 96%
“…Of the three remaining variables, lactate also relates to the acuity of presenting illness while ART non‐adherence or not yet on ART and albumin predominantly relate to HIV disease control and chronicity. In a study that investigated outcomes in HIV‐positive patients admitted to a tertiary‐level hospital ICU, the APACHE II score was shown to overestimate mortality by approximately two‐fold [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in both outpatient and inpatient non-emergency department (ED) settings have indicated that various clinical and laboratory parameters such as the presenting diagnosis, requiring admission to the intensive care unit (ICU), a low CD 4 cell count, an elevated HIV viral load (VL), anaemia, renal dysfunction, albuminaemia, hyperlactataemia etc. have been associated with a higher likelihood of mortality in HIV-positive patients [8][9][10][11][12][13]. However, there is a lack of data emanating from the ED setting.…”
Section: Introductionmentioning
confidence: 99%